Coal Gasification and Coal Microscopic Characteristics in Tanjung Baru, Lahat Regency, South Sumatera - Basuki Rahmad; Sugeng Raharjo; Ediyanto Ediyanto; Gerhana Prasetya Putra (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2020)
The location of research is located in the Tanjung Baru Area, Lahat Regency, South Sumatera. The Geological setting of the Tanjung Baru Area in the South Sumatra Basin is included in the Muara Enim Formation the age is Middle Miocene to Late Miocene. Coal in the Tanjung Baru Area, has a calorific value of 5089-5321 Kcal / kg and is rank High in Bituminous Volatile C-High Volatile Bituminous B according to the ASTM classification. Average quality (proximate test) of Muara Enim Formation coal: total sulphur 0.36-1.49% (adb); 1.28-2,5% ash (adb); inherent moisture 9-11% (adb); volatile matter 38.7-42.4% (adb); fixed carbon 45.5-47.9% (adb), total moisture 28.1-28.8% (Ar); relative density 1.28. Coal Charactersitics of Coal Tanjung Baru  the macerals average are vitrinite (92,4% vol.); liptinite (2.9% vol.); inertinite (5,7% vol.). Each macerals or group macerals has different physical and chemical properties. The variation of composition microscopy showed the changes of plant communities or coal facies leading to varies of coal quality, with a average vitrinite reflectance value 0.47-0.58, generally the coal rank is subbituminous-bituminous. Coal gasification is the process of converting coal into synthesis gas. One of the gas produced is a flammable methane gas. Gasification is raw fuel, in this case coal is partially oxidized to produce a product called combustible gas. The main product from the gasification product is synthesis gas or syngas, consisting of Carbon Monoxide (CO), Hydrogen (H2), Methane (CH4), Carbon Dioxide (CO2) and Nitrogen (N2).